Simulación basada en agentes, del crecimiento vehicular, en proyección a dos décadas en la ciudad de Calceta - Intriago Chichanda, Jhon Alejandro (2016)
The purpose of the research was to estimate vehicle growth through a simulation based on agents, screening two decades in the city of Calceta, to identify possible problems of traffic in the selected areas corresponding to the four main entrances and outputs of this city. It could get with the methodology of the simulation, which began with the definition of the system, in which applied the documentary research and research on the field; it was subsequently formulated a model identifying agents with their characteristics and rules; were collected data by means of observation in a mobile application, to determine the behavior of the agent "vehicle" and develop three models of regression: linear, polynomial, and exponential, that were implemented in the computer using the version 5.3 NEtLogo simulation tool; then, projections of each model with facts of the years 2011 and 2012 were validated for experimentation, where each of the study areas were simulated with each model, to give a criterion based on its interpretation. The results obtained show that if Calceta keeps the same road structure and traffic growth behaves linearly there will be problems of congestion; However, in the worst cases, if it behaves exponentially (most representative according to mean test), the research hypothesis, is accepted as three of the four areas of study will suffer from vehicle congestion after two decades, due to the growth of the urban population.